The dream called overseas : mobility and creative self-exile in fiction by Charlotte Grimshaw, Paula Morris, and Anne Kennedy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University, Albany, New Zealand - Mitchell, Ekaterina (Massey University, 2018)
This thesis investigates how the cultural imaginary of New Zealand is re-examined and redefined through a mobilities paradigm in three contemporary novels by local writers: Charlotte Grimshaw’s Foreign City (2005), Paula Morris’s Queen of Beauty (2002), and Anne Kennedy’s The Last Days of the National Costume (2013). This textual archive evokes and revises mid-century settler cultural nationalist concerns, specifically New Zealand’s perceived cultural and geographical remoteness from the metropolitan centre. Within cultural nationalist discourse, “here and there” were critical geographical and cultural co-ordinates, where “here” referred to a local, derivative reality, while "there” was the centre where history took place. In each of the three novels, the female protagonist moves overseas through a form of creative self-exile, pursuing truthfulness to her artistic nature. However, the characters’ desire for movement takes its origins in patterns of mobility and displacement as experienced by earlier generations. A comparative reading of these novels, alongside a theoretical body of work on mobility, can reveal a unique way in which each writer deals with these concerns, reinterpreting a modernist worldview in the context of the globalised world of the new millennium. Grimshaw approaches literary geography from a semi-ironic angle: although Foreign City deals with a New Zealand artist’s attempt to revisit the inspirational site of Bloomsbury, it is not the real Bloomsbury experience, and thus, it has a distant significance attached to it. For Morris, the remapping project involves inserting Māori cultural aspects into the mobilities paradigm, aligning mobility of stories with mobility of people. In Kennedy’s novel, mobility exposes a settler culture that has failed to live up to its own ideals. Partly set in metropolitan centres, these works of fiction reflect on this country’s settler and immigrant past, proposing an alternative to the modernist European longing that had forged New Zealand’s literary character for several generations. Taken together, this body of contemporary New Zealand fiction indicates the continuing relevance and preoccupation with cultural remarking of distance, isolation, and periphery.
Keywords: Grimshaw, Charlotte; Foreign City; Criticism and interpretation; Morris, Paula; Queen of Beauty; Kennedy, Anne, 1959-; The Last Days of the National Costume; New Zealand fiction; Women authors; New Zealand; Emigration and immigration; Geography in literature; Space in literature